PENERAPAN TEKNIK AUDIT BERBANTUAN KOMPUTER DAN COMPUTER SELF EFFICACY PADA KINERJA AUDITOR - Girinatha Surya, I Gede; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
This study was to determine the effect of the application of Computer Assisted Audit Techniques (CAATs) and Computer Self Efficacy (CSE) on the performance of auditors.This study uses Computer Assisted Audit Techniques and Computer Self Efficacy as independent variables and the performance of auditors as the dependent variable. The variable in this study was measured using a questionnaire with 4 Likert scale. This study was conducted in public accounting firms that are members of the Indonesian Institute of Certified Public Accountants (IAPI) area of ??Bali. Data was collected by distributing questionnaires to auditors as respondents using purposive sampling method of sampling. Techniques of analysis using multiple linear regression analysis.These results indicate that the variable Computer Self Efficacy Computer Assisted Audit Techniques and significant positive effect on the performance of auditors.
Keywords: Computer Assisted Audit Techniques, Computer Self Efficacy, the performance of auditors